Electrical double layer capacitor with proton conducting kappa-carrageenan-chitosan electrolytes - Majid, Siti Rohana; Arof, Abdul Kariem; Shuhaimi, N.E.A.; Alias, N.A. (World Scientific Publishing, 2008)
Charge-discharge characteristics of electrical double layer capacitors (EDLCs)using kappa-carrageenan-chitosan based electrolyte is the focus of the present work. Chitosan and kappa-carrageenan were blended to obtain films with high mechanical strength. The room temperature conductivity of 0.5 g chitosan + 0.5 g kappa-carrageenan (CCPA) film and 0.5 g chitosan + 0.5 g kappa-carrageenan + 0.1765 g ammonium nitrate(CCPAAN) film are (1.38 +/- 0.36) x 10(-6) S cm(-1) and (2.39 +/- 0.83) x 10(-4) S cm(-1), respectively. The conducting species is H(+) and conduction occurs via a Grotthuss mechanism. The resistance of the phenol resin based activated carbon electrode film is between 15 to 20 Omega. The capacitance of the EDLCs is stable over 20 cycles. The average discharge capacitance of the EDLC employing CCPAAN electrolyte and activated carbon electrodes is between 13 to 18.5 F g(-1).